2012
DOI: 10.1002/mnfr.201100555
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐existent Hsp72 contributes to glutamine‐induced hepatic hsp72 gene activation during heat shock recovery period in rat

Abstract: Glutamine switched on alteration pathway in inducing hsp72 gene activation. The existence of Hsp72 plays a critical role in the reactivation of hsp72 gene. Glutamine sustained the induction of intracellular Hsp72, which could be beneficial in protecting the liver from various injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On the contrary, Gln associated to HSP27 induction, an eff ect similar to that previously reported in rats with d-galactosamine/lipopopysaccharide-induced liver injury receiving biclycol [6]; this result support s role of HSP27 in Gln-mediated hepatoprotection. Other authors have also observed a modulating eff ect of Gln on heat shock proteins in rat livers submitted to intestinal ischemia-reperfusion and during the heat shock recovery period [31,32].…”
Section: Discussionmentioning
confidence: 86%
“…On the contrary, Gln associated to HSP27 induction, an eff ect similar to that previously reported in rats with d-galactosamine/lipopopysaccharide-induced liver injury receiving biclycol [6]; this result support s role of HSP27 in Gln-mediated hepatoprotection. Other authors have also observed a modulating eff ect of Gln on heat shock proteins in rat livers submitted to intestinal ischemia-reperfusion and during the heat shock recovery period [31,32].…”
Section: Discussionmentioning
confidence: 86%
“…Although glutamine is able to slightly increase HSF1 trimerization in non-stressful situations [49,56], glutamine acts physiologically as an enhancer of the HS response, which means that a pre-existent (e.g., exercise, heat stress, elevated sympathetic nervous system tonus) stress-induced HSF1 activation must be present for glutamine to fully enhance HSF1 activation and transcribing activity. In addition, iHSP70 per se participates in glutamine-induced HS response [252].…”
Section: Glutamine Metabolism and Its Importance For The Heat Shock Rmentioning
confidence: 99%